Occurrence and biosynthesis of cytokinins in poplar - Jaworek, Pavel; Kopečný, David; Zalabák, David; Šebela, Marek; Kouřil, Štěpán; Hluska, Tomáš; Končitíková, Radka; Podlešáková, Kateřina; Tarkowski, Petr (Planta, 2019)
Isoprenoid and aromatic cytokinins occur in poplar as free compounds and constituents of tRNA, poplar isopentenyltransferases are involved in the production of isoprenoid cytokinins, while biosynthesis of their aromatic counterparts remains unsolved. Cytokinins are phytohormones with a fundamental role in the regulation of plant growth and development. They occur naturally either as isoprenoid or aromatic derivatives, but the latter are quite rare and less studied. Here, the spatial expression of all nine isopentenyl transferase genes of Populus × canadensis cv. Robusta (PcIPTs) as analyzed by RT-qPCR revealed a tissue preference and strong differences in expression levels for the different adenylate and tRNA PcIPTs. Together with their phylogeny, this result suggests a functional diversification for the different PcIPT proteins. Additionally, the majority of PcIPT genes were cloned and expressed in Arabidopsis thaliana under an inducible promoter. The cytokinin levels measured in the Arabidopsis-overexpressing lines as well as their phenotype indicate that the studied adenylate and tRNA PcIPT proteins are functional in vivo and thus will contribute to the cytokinin pool in poplar. We screened the cytokinin content in leaves of 12 Populus species by ultra-high performance-tandem mass spectrometry (UHPLC-MS/MS) and discovered that the capacity to produce not only isoprenoid, but also aromatic cytokinins is widespread amongst the Populus accessions studied. Important for future studies is that the levels of aromatic cytokinins transiently increase after daybreak and are much higher in older plants.
Keywords: listy rostlin; Topolin; tRNA; Arabidopsis; fylogeneze; tandemová hmotnostní spektrometrie; Phylogeny; Populus; Cytokinin; regulátory růstu rostlin; Isopentenyltransferase; rostlinné proteiny; Cytokinins; Expression; cytokininy; Plants, Genetically Modified; Plant Growth Regulators; Plant Leaves; Poplar; geneticky modifikované rostliny; Alkyl and Aryl Transferases; Tandem Mass Spectrometry; alkyltransferasy a aryltransferasy; Plant Proteins